Food Insecurity, Self-rated Health, and Obesity among College Students. Issue 4 (4th July 2017) - Knol, Linda L.; Robb, Cliff A.; McKinley, Erin M.; Wood, Mary
ABSTRACT: Background : The prevalence of food insecurity among college students ranges from 14% to 59%. Most of the research to date has examined the determinants of food insecurity.Purpose : The purpose of this study was to examine the relationships between food insecurity and self-rated health and obesity among college students living off campus.Methods : An online survey was sent to students 19 years of age or older. Food security status was measured using the Adult Food Security Survey Module. Health status, height, and weight were self-reported. Two logistic regression analyses assessed the associations between food insecurity and the 2 dependent variables, health status and overweight/obesity.Results : A sample of 351 students provided valid responses to the questions used in these analyses. Food insecurity was not associated with obesity. Food insecure students had significantly higher rates of fair/poor health when compared to their food secure counterparts (odds ratio [OR] = 2.1, 95% confidence interval [CI], 1.1, 4.3).Discussion : Food insecurity is related to self-rated fair/poor health but not overweight/obesity in college students living off campus.Translation to Health Education Practice : Health Educators on college campuses should be cognizant of financial conditions that may place students at risk for food insecurity.